2019
DOI: 10.3390/jcm8111909
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Peri-Implantitis—Electrolytic Cleaning Versus Mechanical and Electrolytic Cleaning—A Randomized Controlled Clinical Trial—Six-Month Results

Abstract: Objectives: The present randomized clinical trial assesses the six-month outcomes following surgical regenerative therapy of periimplantitis lesions using either an electrolytic method (EC) to remove biofilms or a combination of powder spray and electrolytic method (PEC). Materials and Methods: 24 patients with 24 implants suffering from peri-implantitis with any type of bone defect were randomly treated by EC or PEC. Bone defects were augmented with a mixture of natural bone mineral and autogenous bone and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…The regenerative potential of horizontal bone defects with no walls is worse than for contained, multi-walled defects [4,7]. In this animal study we observed massive horizontal bone loss and merging defects resulting in a severely resorbed ridge (Figure 3).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The regenerative potential of horizontal bone defects with no walls is worse than for contained, multi-walled defects [4,7]. In this animal study we observed massive horizontal bone loss and merging defects resulting in a severely resorbed ridge (Figure 3).…”
Section: Discussionmentioning
confidence: 66%
“…This paper does not investigate the reasons for this observation. In the context of previous literature, it may be assumed that EC in contrast to CC removes the bacterial biofilm and other remnants to an extent that makes complete re-osseointegration possible [6,7]. The latter was proven through histology ( Figures 5-8).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, complete decontamination around infected implant surfaces requires the clinical attention to achieve implant success. Electrolytic cleaning needs mechanical cleaning for complete removal of organic contaminants to achieve re-osseointegration in infected implants [ 28 ]. Without any mechanical cleaning, the optimized electrochemical treatment was able to achieve complete decontamination on the contaminated metal surface in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the cleaning of the implant remains a critical pillar of any successful treatment, and promising developments in this field may also lead to optimized processes. One example, for instance, is the use of electrolytic systems to clean the implant surface (49). However, to date, no evidencebased justification of such treatment is available.…”
Section: Future Developmentsmentioning
confidence: 99%